(untitled) (Baghdad Science Journal, 2019)
In this paper fractional Maxwell fluid equation has been solved. The solution is in the Mettag-Leffler form. For the corresponding solutions for ordinary Maxwell fluid are obtained as limiting case of general solutions. Finally, the effects of different parameters on the velocity and shear stress profile are analyzed through plotting the velocity and shear stress profile.